The Influence of Product Quality, Price and Brand Image on Decision to Purchase Matic Honda Scoopy Motorcycles during the Pandemic Period in Wanasari Village, Sungai Loban District, Tanah Bumbu Regency - NiPutuNitaLestari; SetioUtomo; Fitriyadi; SitiRusidah (Journal of Business Transformation and Strategy, 2024)
Abstract: This study aims to examine and determine the effect of product quality, price, and brand image on purchasing decisions of Honda Scoopy automatic motorcycles during the pandemic in Wanasari Village, Sungai Loban District, Tanah Bumbu Regency. The research approach used is a quantitative approach. Samples were taken as many as100 respondents who were selected using purposive sampling technique. Collecting data using questionnaire while data analysis using multiple linear regression. testing and data processing using SPSS version 26.0. The results showed that partially the Product Quality variable (X1) had a significant effect on purchasing decisions for Honda Scoopy   motorcycles with a significant level of 0,000<0,05and the t value of 7.7733 > t table 1.984 with a large effect of 38,3%, Price (X2) has a significant effect on purchasing decisions for Honda Scoopy motorbikes with a significant level of 0,000<0,05 and the t value of 13,843 t table 1,984 with a large influence of 43,8%, Brand Image (X3) has a significant effect on the decision to purchase a Honda Scoopy motorcycle with a significant level of 0,024<0,05 and a the t value of 2.289 > t table 1.984 with a large effect of6,4%. And simultaneously the variables of product quality (X1), price (X2), and brand image(X3) have a significant effect on purchasing decisions (Y) with a significant value of 0,000<0,05and and the value of f count 246.20 > f table 2,70 with a large the effect is 88,5%